Mechanisms linking empagliflozin to cardiovascular and renal protection. (15th August 2017) - Perrone-Filardi, Pasquale; Avogaro, Angelo; Bonora, Enzo; Colivicchi, Furio; Fioretto, Paola; Maggioni, Aldo Pietro; Sesti, Giorgio; Ferrannini, Ele
Abstract: In patients with type 2 diabetes mellitus (T2DM), the main cause of morbidity and mortality is cardiovascular (CV) disease. Diabetic kidney disease, which develops in approximately 40% of patients with T2DM, further increases the risk of CV-related morbidity and mortality. The sodium glucose co-transporter 2 (SGLT2) inhibitor empagliflozin, which provides effective glycaemic control as either monotherapy or as an add-on to other glucose-lowering agents in patients with T2DM, was also shown to improve CV and renal outcomes in the large, randomised, placebo-controlled EMPA-REG OUTCOME trial in patients with T2DM at high risk of CV events. The underlying mechanisms for the CV and renal protective effects of empagliflozin are not fully understood, but are likely to involve a combination of several mechanisms, including empagliflozin-associated body weight and blood pressure reductions, diuresis, a shift in substrate utilisation and activation of tubuloglomerular feedback. The results of ongoing CV outcomes trials with other SGLT2 inhibitors will potentially confirm whether the beneficial CV and renal effects observed in EMPA-REG OUTCOME are unique to empagliflozin or are a drug class effect.